Case reports Interstitial brachytherapy for liver metastases and assessment of response by positron emission tomography: a case report - Sharma, Daya Nand; Thulkar, Sanjay; Kumar, Rakesh; Rath, Goura Kishor (Journal of Contemporary Brachytherapy, 2010)
For liver metastases (LM), image guided percutaneous ablative procedures such as radiofrequency ablation (RFA), laser induced thermal therapy (LITT) and trans-arterial chemo-embolisation (TACE) are increasingly being used because they are relatively safer, less invasive and equally effective. CT scan guided interstitial brachytherapy (IBT) with a single large dose of radiation by high dose rate (HDR) brachytherapy is a novel technique of treating LM and has shown good results. Positron emission tomography (PET) scan may provide better information for assessing the response to IBT procedures. We hereby report a case of LM that was treated by HDR IBT and PET scan was done in addition to CT scan for assessing the response.